The impact of gratitude interventions on patients with cardiovascular disease: a systematic review - Wang, Xiaoxiao; Song, Chunli (Frontiers in Psychology, 2023)
Positive psychological factors play a pivotal role in improving cardiovascular outcomes.Gratitude not only promotes mental health but also improves cardiovascular outcomes. Gratitude may have a positive impact on biomarkers regarding cardiovascular risk, cardiovascular function, and the autonomic nervous system (ANS). Gratitude interventions are known to be one of the most effective positive psychological interventions, with potential clinical applications in cardiology practice. However, there is limited research focusing on this aspect. This paper reviews the concept of gratitude, the association between gratitude and cardiovascular diseases, and the effects of gratitude on cardiovascular diseases and related mechanisms. This review further aimed to advance the clinical effects of gratitude.Based on existing research, we acknowledged areas important for future research regarding the impact of gratitude for the field of cardiovascular diseases and potential novel clinical treatments of cardiovascular diseases.